Proven prevention tools for addressing STI epidemics - Anatole S. Menon-Johansson (BMC, 2018)
Abstract The ongoing rise of sexually transmitted infections (STIs) poses a global public health challenge and the risk of acquiring one of these infections depends upon sexual practices, the number of sexual encounters and the location of that individual within the sexual network. Commercial sex workers (CSWs) have potentially a pivotal role in the transmission of STIs; however, a new study presented in this journal describes markers of risk but no increase in infections amongst men who pay for sex (MPS). This commentary highlights some of the growing evidence regarding STI prevention and the value of using these tools to protect CSWs, their clients and by extension the sexual partners of MPS.